Prevalence of azithromycin resistance after the COVID-19 era in clinical bacterial isolates from a tertiary care hospital in Gurugram, India - Debnath, Parbati; Alam, Md Fahim; Khandait, Manisha; Husain, Fohad Mabood; Munawar, Nayla; Mondal, Aftab Hossain (Frontiers in Microbiology, 2025)
The increasing prevalence of antibiotic resistance in pathogenic bacteria poses a great healthcare problem worldwide. Azithromycin (AZM) is a very effective macrolide antibiotic to treat many bacterial infections, but increasing azithromycin resistance in clinical bacteria decreases the effectiveness of this vital antibiotic, which is a major concern. The primary aim of the present study was to investigate the prevalence of azithromycin resistance and the occurrence of mphA gene in bacteria isolated from various clinical samples in Gurugram, India. For this, 138 pure bacterial isolates were obtained from the Department of Microbiology, Faculty of Medicine and Health Sciences, SGT Medical College, Hospital & Research Institute, Gurugram, India, from February to June 2024. All the isolates were identified by VITEK 2 system, and E. coli (22.5%) was found to be the most common pathogen in urine samples. Screening for azithromycin resistance by agar dilution and minimum inhibitory concentration (MIC) method found 30 azithromycin-resistant bacterial isolates. The present study found the prevalence of azithromycin resistance in pathogenic bacteria from clinical samples is 22%, indicating an increase in prevalence after the COVID-19 era, which is a major concern. Antibiotic profiling data revealed that 100% of the azithromycin-resistant isolates were multidrug-resistant, which is a serious issue. Furthermore, plasmid-mediated mphA gene was successfully amplified by the PCR method from 11 bacterial isolates, which may be responsible for azithromycin resistance. Our findings indicate the rapid emergence of azithromycin resistance in pathogenic bacteria, highlighting the urgency of stringent surveillance and control measures.